Two new species of aquatic dance-flies of the genus Wiedemannia Zetterstedt, 1838 (Diptera: Empididae) from the Caucasus - S.Yu. Kustov; D.A. Zherebilo (Кавказский энтомологический бюллетень, 2014)
Currently, eleven species of the aquatic dance flies of the genus Wiedemannia Zetterstedt, 1838 are known from the Caucasus including 2 new species described in this paper: W. beckeri (Mik, 1889), W. braueri (Mik, 1880), W. caucasica Joost, 1981, W. chvalai Joost, 1981, W. fallaciosa (Loew, 1873), W. klausnitzeri Joost, 1981, W. pseudovaillanti Joost, 1981, W. shamshevi sp. n. (Russia: Karachay-Cherkessian Republic, South Ossetia), W. sinclairi sp. n. (Russia: Krasnodar Province), W. vaillanti Joost, 1981 and W. zetterstedti (Fallén, 1826).